Epidemiological and prognostic single center study of anal carcinoma - Alrubai,Alaa Mobder Mohammed (2020)
Abstract Background: Anorectal carcinoma includes the anal margin, the anal canal, and the lower rectum. The incidences of anal tumors represent 1.4 % of all gastrointestinal tumors. Patients and methods: Our study is retrospective and was conducted at Baghdad Medical City. Patient’s data were collected from the medical records through a predesigned sheet that included the following information: demographic data, medical history, past-history, presenting symptoms, pathological data, and treatment details. Results: The median age was 49 years. As regard tumor extension, 85.71 % of patients had anal disease, while anorectal cancer was encountered in 14.28 % of cases only. Male to female ratio was 1:3. Most of cases were SCC 78.57 %. Only 11 patients (39.28 %) were diagnosed as Stage I, whereas 12 patients (42.85 %) had Stage II-III disease. Moderate differentiated tumors are the most common. The tumor mass located between 5-10 cm das a distance from anal verge in 12 (42.85 %) of patients. We found 6 (21.42 %) patients with positive virology tests with no specificity detected. APR was the mainstay for treatment of stage I disease. Neoadjuvant treatment followed by TME resection was the treatment found in locally advanced tumors. The mean Overall Survival (OS) for patients received neoadjuvant CRT in the study was 43.5 months, while, the mean OS was 45.73 months in the adjuvant setting. Univariate analysis for OS according to prognostic factors revealed that sites of cancer, grades and histopathology were significant independent prognostic factors for OS in this study. The anal canal tumor was associated with shorter OS (33.25) months in comparison to the anorectal cancer (OS = 47.22 months). Based on tumor grade, well and moderate differentiation have better OS (60.21 months) while, poorly grade was associated with shorter OS (43.07 months). On the concern of SCC, it was associated with shorter OS (37 months) in comparison to higher survival in patients with adenocarcinoma (46.13 months). Conclusion: Anal canal cancer has poorer prognosis than anorectal. The early-stage has a better OS that needs more effort for early diagnosis and treatment.